(untitled) - Bitton, Gabriel (Hoboken, N.J., 2011)
Includes bibliographical references and index
Keywords: Sanitary microbiology; Water -- Microbiology; Sewage -- Microbiology; Water Microbiology; Water Purification -- Methods; Vi sinh học vệ sinh; Nước -- Vi sinh học; Nước thải -- Vi sinh học; Vi sinh vật nước; Lọc nước -- Phương pháp